Basel III and recourse to Eurosystem monetary policy operations - Annalisa Bucalossi; Cristina Fonseca Coutinho; Kerstin Junius; Alaoishe Luskin; Angeliki Momtsia; Imene Rahmouni-Rousseau; Benjamin Sahel; Antonio Scalia; Stefan Schmitz; Rita Isabel Prior Soares; Franziska Schobert; Michael Wedow (European Central Bank (ECB), 2016)
Following the emergence of the financial crisis in August 2007, the Basel Committee on Banking Supervision established in 2010 a new global regulatory framework. In addition to raising capital requirements, it introduced three ratios, two of which set out minimum standards for liquidity and funding risk, i.e. the liquidity coverage ratio and the net stable funding ratio, and one which aims to limit leverage in the banking system, i.e. the leverage ratio. All three ratios can have a number of implications for monetary policy implementation, in particular the liquidity coverage ratio and the net stable funding ratio owing to the special role of central banks in providing liquidity. This paper investigates the extent to which the regulatory initiatives might have already had an impact on banks' behaviour in Eurosystem monetary policy operations. It also provides an overview of the regulatory state of play and major recent advancements in banks' compliance with the three Basel III ratios. Based on aggregate data, the empirical evidence generally supports some of the theoretically predicted effects of the three ratios. However, no firm conclusions can be drawn as to whether the introduction of the three ratios could cause a significant change in banks' recourse to Eurosystem monetary policy operations. This is partly due to the fact that, in aggregate, major developments, such as substantial fluctuations in the recourse to Eurosystem refinancing operations in the years between 2012 and 2015, have been driven by the financial crisis and the gradual recovery from it, as well as by the accommodative stance of monetary policy.
Keywords: G28; E58; 330; Basel III; liquidity regulation; monetary policy implementation